Natural Convection Flow of Nanofluids in Squeeze Film with an Exponential Curvature - P., Vimala; K., Manimegalai (Journal of Informatics and Mathematical Sciences, 2010)
A theoretical study of the laminar squeeze flow of copper water and alumina water nanofluids between a flat circular stationary disk and a curved circular moving disk is carried out using energy integral method. The squeeze film behaviour is examined analytically and the effects of inertia and curvature on the squeeze film pressure, load carrying capacity of the fluid and temperature are analysed. Further, the problem is solved numerically for a sinusoidal motion of the upper curved disk taking an exponential form of the gap width. It is found that the copper water nanofluid is better than alumina water nanofluid for better heat transfer rates. While high inertia forces strongly influence the squeeze film behaviour, low inertia forces are favourable for temperature distribution. Further, concave nature of the upper disk gives better squeeze film characteristics than convex disk. However, convex disk is better than concave disk as far as the temperature distribution is concerned.